Influence of Sample Preparation on SERS Signal - Bianchi-Carvalho, Isabela [UNESP]; Oliveira, Marcelo José dos Santos [UNESP]; Martin, Cibely Silva [UNESP]; Sánchez-Cortés, Santiago; Constantino, Carlos José Leopoldo [UNESP] (MDPI, 2025)
Carbendazim (MBC), a commonly used fungicide from the benzimidazole group, was applied in this study as a probe molecule to understand the influence of sample preparation on the SERS (surface-enhanced Raman scattering) signal. We applied the external standard method (ESM), preparing fresh Ag colloid samples (reduced by hydroxylamine) for each concentration and measuring with and without potassium nitrate (KNO₃) as an aggregation-inducing salt. The impact of sample dilution before or after the addition of the salt to the Ag colloid was also explored. SERS signals were correlated with Ag colloid aggregation observed via transmission electron microscopy (TEM), UV-Vis extinction, dynamic light scattering (DLS), and zeta potential, examining diffusion-limited cluster aggregation (DLCA) and reaction-limited cluster aggregation (RLCA) mechanisms. The optimal results were achieved without KNO₃, with more compact aggregates at lower concentrations and more branched ones at higher concentrations. Dilution of the Ag colloid before salt addition enabled lower detection limits than without any dilution. No SERS signal was observed when the salt was added before dilution. These findings emphasize that a consistent relationship between aggregate morphology and the SERS signal cannot be generalized across analytes. Analyte-specific properties play a crucial role in determining optimal aggregation conditions for SERS analysis.
Keywords: aggregation mechanism; carbendazim; detection; SERS